S129 Progenitor cell-derived basophil activation test (PCBAT) predicts clinical reactivity in cat allergic asthmatics- a proof of concept study. (12th November 2019) - Bennett, M; Wu, J; Murray, CS; Gauvreau, G; Cusack, R; Bulfone-Paus, S; Simpson, A
Abstract : Many allergic asthmatics who are sensitized to cat (on skin prick or IgE testing) deny symptoms of asthma or allergy on contact with cats. Clinical reactivity to cat can be measured using inhaled allergen challenge, but this is not widely available in clinical practice and is not appropriate in poorly controlled asthma. We are investigating whether we can predict clinical reactivity to cat allergen using an in vitro high throughput effector cell assay (progenitor cell-derived basophil activation test -PCBAT). Methods: We performed inhaled allergen challenge on 17 adults who were skin prick positive to cat. Participants inhaled cat allergen (McMaster, Ontario) at increasing concentrations until forced expiratory volume in 1 second (FEV1 ) dropped > 20% from baseline. The early airway response 0–2 hours after allergen exposure was measured as a percentage drop from baseline FEV1 against time (EARAUC0-2hrs ). We divided the maximum percentage drop in FEV1 and also the EARAUC0-2hrs by the cumulative dose of inhaled allergen to give a dose response slope (DRS) and EARAUC0-2hrs per allergen unit. We developed PCBAT using well characterized human CD34+ progenitor cell-derived basophils, which were passively sensitized with sera from the 17 adults. The cultures were stimulated with increasing concentrations of cat allergen. Degranulation was quantified by flow cytometry using CD63 to mark activation. Results presented as area under the curve (PCBATAUC). Results: In PCBAT we saw a dose-dependent increase in CD63 expression on flow cytometry with a range of AUC (>600 fold, Panel A). On cat allergen challenge, the cumulative dose inhaled to cause a 20% drop in FEV1 and subsequent airway recovery also varied. We saw a significant correlation between PCBATAUC and the total cumulative dose of inhaled allergen (r=-0.56, p=0.019), the DRS (r=0.54, p=0.026) and also the EARAUC0-2hrs per allergen unit (r=0.51, p=0.038) (Panel B). Conclusions: Our novel in vitro high throughput effector cell assay (PCBAT), predicted clinical responsiveness to inhaled cat allergen in multiple clinical measures. PCBAT may provide a safe alternative to inhaled allergen challenge in asthma. Further work is required to confirm these findings and to determine the place of this test in clinical practice.